PENGARUH PEMBELAJARAN AQIDAH AKHLAQ TERHADAP AKHLAQUL KARIMAH SISWA DI MADRASAH TSANAWIYAH AL-AZHAR TOKET PROPPO PAMEKASAN TAHUN PELAJARAN 2022/2023 - Munib, Abdul; Atnawi, Atnawi (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
The problem at the heart of the research is the influence and magnitude of the influence of Aqidah Akhlaq learning on the Akhlaqul Karimah of students at MTs Al-Azhar Toket Proppo Pamekasan? This research uses a quantitative approach with analysis using the product formula formula, data confirmation is carried out through interviews, and observation. Interviews were conducted with Aqidah Akhlah teachers. The questionnaire was distributed to 56 students in grades VII, VIII and IX and used as research objects. In collecting data, both interviews, observations and distributing questionnaires went smoothly, all questions asked could be answered in accordance with the actual conditions and reality at MTs Al-Azhar so that the data collected could be used as an accurate source in writing this thesis. The results of this research show that, firstly, there is an influence of Aqidah Akhlaq learning on the Akhlaqul Karimah of students at Madrasah Tsanawiyah Al-Azhar. This is proven by the r work value of 0.75 which is greater than the r product moment table, both at the 5% significance level, namely 0.263 and 1%, namely 0.342. Second, Aqidah Akhlaq learning has quite an influence on the morals of students at MTs Al-Azhar, this is It is proven that the working r of 0.75 is in the range of 0.600 to 0.800 with a Fair interpretation. The implications of this research are: a) The importance of learning Aqidah Akhlak, b) Development of learning materials, c) Strengthening teacher training, d) Development of extracurricular activities, e) Collaboration with parents and the community.